Auxiliary digital control unit for capacitor banks - Nunes, Patricia (2020)
This paper addresses the conception of a prototype based in an implementation of a microcontroller proposed as an alternative solution to programmable logic controllers for controlling a capacitor bank. The control considered is in accordance with the Portuguese Energy Services Regulatory Authority. The prototype uses information concerned with the date and time for the accomplishment of industrial schedules. The equipment for the prototype is implemented on a printed circuit board designed and tested for industrial application and is in accordance to current standards for harmonic disturbances.